A case study of integrating a proprietary evaluation system into the failure analysis processes of optical sensors. (January 2018) - Samson, Armien John; Mabayo, Jed Neil; Frieszer, Patrick; Ang, Lou Benedict
Abstract: This paper presents a new and novel approach in characterizing and verifying failure mechanisms of optical sensors using a patter-driven, real-time evaluation tool, whose initial purpose is to address automated characterizations and validations. The goal of this paper is to create a series of programs that are specifically aimed at understanding the optical failure parameters of optical sensors. The devices were then subjected to full failure analysis process to correlate and verify the results obtained. Preliminary results showed that this approach: (a) significantly shortens the cycle time of the FA process of optical sensors as complicated test set-ups in the automatic test equipment (ATE) can be turned into a secondary verification tool; (b) provides better understanding of the optical as well as the electrical failures of optical sensors since the programming of our automated evaluation system can be adjusted to explore different failure characterizations and evaluations; and (c) it optimizes the failure analysis process by providing the analyst with more data and information about the device failures.